2005
DOI: 10.1016/j.bbadis.2005.04.004
|View full text |Cite
|
Sign up to set email alerts
|

JNK and PI3k/Akt signaling pathways are required for establishing persistent SARS-CoV infection in Vero E6 cells

Abstract: Persistence was established after most of the SARS-CoV-infected Vero E6 cells died. RNA of the defective interfering virus was not observed in the persistently infected cells by Northern blot analysis. SARS-CoV diluted to 2 PFU failed to establish persistence, suggesting that some particular viruses in the seed virus did not induce persistent infection. Interestingly, a viral receptor, angiotensin converting enzyme (ACE)-2, was down-regulated in persistently infected cells. G418-selected clones established fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 20 publications
3
92
0
Order By: Relevance
“…There is also an increasing body of literature showing that JNK activation follows bacterial, fungal, prion, parasitic, or viral infections. Under these circumstances, JNK activation may influence important cellular consequences, such as alterations in gene expression (1,53,59,162,167,176,199,294,325,326,346), cell death (58,89,137,139,169,193,243,293), viral replication, persistent infection or progeny release (215,224,251,260), or altered cellular proliferation (178). The exact mechanism of JNK activation under each of these circumstances remains to be elucidated fully, although there may be involvement of Toll-like receptors, direct pathway modulation through interaction with upstream protein regulators, or the activation following an ER stress response (79,87,110,124,143,191,253,261,279,294,312).…”
Section: Fig 1 Overview Of the Jnk Pathway (A)mentioning
confidence: 99%
“…There is also an increasing body of literature showing that JNK activation follows bacterial, fungal, prion, parasitic, or viral infections. Under these circumstances, JNK activation may influence important cellular consequences, such as alterations in gene expression (1,53,59,162,167,176,199,294,325,326,346), cell death (58,89,137,139,169,193,243,293), viral replication, persistent infection or progeny release (215,224,251,260), or altered cellular proliferation (178). The exact mechanism of JNK activation under each of these circumstances remains to be elucidated fully, although there may be involvement of Toll-like receptors, direct pathway modulation through interaction with upstream protein regulators, or the activation following an ER stress response (79,87,110,124,143,191,253,261,279,294,312).…”
Section: Fig 1 Overview Of the Jnk Pathway (A)mentioning
confidence: 99%
“…Furthermore, the use of signal transduction pathways modulators, either singly (Yang et al, 2005a,b;Reeves et al, 2005) or in combination, could be the most appropriate therapeutic strategy. In fact, it has been shown that SP600125 used together with inhibitors of phosphatidylinositol 3-kinase/Akt prevented the establishment of persistent SARS-CoV infection (Mizutani et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…W. Dong, et al Antiviral Research 173 (2020) 104651 2015; Kindrachuk et al, 2015;Lee et al, 2016;Mizutani et al, 2005). Nevertheless, no studies to date have focused on detecting global phosphorylation events in host cells during CoV infection.…”
Section: The Phosphorylation Involved In the Host Response To Tgev Inmentioning
confidence: 99%
“…Yang et al found that PEDV infection stimulated the activation of EGFR and its downstream STAT3 cascade, which increased viral infection by negatively regulating type I interferon (IFN-I) signaling (Yang et al, 2018). The ERK/MAPK and PI3K/AKT/mTOR signaling responses play important roles in MERS-CoV infection (Kindrachuk et al, 2015), and JNK and phosphatidylinositol 3′-kinase (PI3K)/Akt are required for establishing persistent SARS-CoV infection in Vero E6 cells (Mizutani et al, 2005). Our phosphoproteomic analysis found that TGEV infection enhanced (A and E) Effect of inhibitors on viral yields.…”
Section: P38 Is One Of the Targets For The Inhibitory Activity Of A9 mentioning
confidence: 99%
See 1 more Smart Citation